2010
DOI: 10.1002/jsfa.4172
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of dried safflower petal aqueous extract and its main constituent, carthamus yellow, against lipopolysaccharide-induced inflammation in RAW264.7 macrophages

Abstract: These results suggest that SFA and CY provide an anti-inflammatory response through inhibiting the production of NO and PGE(2) by the downregulation of iNOS and COX-2 gene expression. Thus safflower petals have the potential to provide a therapeutic approach to inflammation-associated disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…It is a natural, edible pigment approved in China and as a state-level new drug. Recently, Chinese and foreign scholars have conducted extensive and in-depth studies on the extraction and pharmacological effects of SY Xi et al, 2012), and found that SY is not only a valuable natural edible pigment, with the advantages of attractive color, resistance to high temperatures, high pressure, low temperature, light, acid, and reduction, and antimicrobial properties, but also has many pharmacological properties such as expansion of coronary arteries, antioxidation, myocardial protection, lowering of blood pressure, immune suppression, and cerebral protection (Wang et al, 2011;Chen et al, 2012). In this study, we examined the effect of SY on the blood lipids of hyperlipidemic mice and the in vitro synthesis of cholesterol to provide a basis for its pharmacological applications.…”
Section: Introductionmentioning
confidence: 99%
“…It is a natural, edible pigment approved in China and as a state-level new drug. Recently, Chinese and foreign scholars have conducted extensive and in-depth studies on the extraction and pharmacological effects of SY Xi et al, 2012), and found that SY is not only a valuable natural edible pigment, with the advantages of attractive color, resistance to high temperatures, high pressure, low temperature, light, acid, and reduction, and antimicrobial properties, but also has many pharmacological properties such as expansion of coronary arteries, antioxidation, myocardial protection, lowering of blood pressure, immune suppression, and cerebral protection (Wang et al, 2011;Chen et al, 2012). In this study, we examined the effect of SY on the blood lipids of hyperlipidemic mice and the in vitro synthesis of cholesterol to provide a basis for its pharmacological applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, after exposure to a stimuli, such as LPS, IκBα phosphorylation increases, which triggers its proteolytic degradation, leading to NF-κB activation and the expression of genes that play important roles in innate and adaptive immunity. 43,44 Interestingly, hBD3-3 blocks phosphorylation-induced IκBα degradation, thereby inhibiting the nuclear migration of NF-κB p65 subunits ( Figure 6). Based on these results, we suggest that hBD3-3 possesses outstanding anti-inflammatory activity through its targeting of canonical NF-κB pathway-mediated inflammation in cells.…”
mentioning
confidence: 98%
“…The reactive free radical NO, which is synthesized by iNOS, is a major macrophage-derived inflammatory mediator and has also been reported to be involved in the development of inflammatory diseases. PGE 2 is an other import anti-inflammatory mediator and is produced from arachidonicacid metabolites by the catalysis of Cyclooxygenase-2 (COX-2) [21]. Thus, we investigated the anti-inflammatory activities of E. cava enzymatic extract and AG-DK on LPS-induced NO and PGE 2 production in murine macrophage RAW 264.7 cells.…”
Section: Resultsmentioning
confidence: 99%